An Agenda for Improving the Teaching of Economics - Bach, G. L. (American Economic Review, 1973)
This Committee the Association's Committee on Economic Education is charged to help improve the teaching of economics. This is obviously a many-faceted problem, and at most a committee like this can expect to play only a modest role in prodding, stimulating innovation, encouraging, and providing help on some fronts. During the past decade the Committee has attempted especially to stimulate research on the effectiveness of alternative teaching approaches, to stimulate attention to the teaching process, and to raise the prestige of teaching at the college level. These attempts are documented elsewhere.1 Building on them, we now suggest some next steps.